Prevalence, mortality, and resource utilization of Staphylococcus aureus bacteremia in liver transplant recipients: A 2012-2016 nationwide analysis - Jahanavi M. Ramakrishna; Atulya Aman Khosla; Paul T. Kröner; Bhaumik Brahmbhatt; Fernando F. Stancampiano; Claudia R. Libertin (Elsevier, 2022)
Background: Bacteremia due to Staphylococcus aureus is a known, serious complication of liver transplantation (LT). Objectives: The purpose of our study was to evaluate the national impact of S. aureus bacteremia (SAB) in LT recipients in terms of mortality rates and the economic impact on an institution. Methods: This retrospective cohort study used 2012-2016 National Inpatient Sample data, the largest public inpatient database in the United States, to separate LT recipients with SAB during index LT admission from those unaffected by SAB. The SAB cohorts are further defined by speciation, methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA). The primary outcome was the odds of inpatient mortality. Secondary outcomes included inpatient morbidity, resource utilization, hospital length of stay, and inflation-adjusted total hospital costs and charges. Results: During the study period, 26,415 patients underwent LT. SAB was found in 340 patients (MSSA n = 180 [52.9%], MRSA n = 160 [47.1%]), while 26,075 LT patients had no SAB episode during the index admission. Patients with MSSA and MRSA bacteremias displayed higher inpatient mortality rates (11.1% and 9.4%, respectively) compared to the non-SAB cohort (3.4%, p < 0.01). Conclusions: During the index LT hospitalization, SAB was directly correlated with increased mortality rates, sepsis occurrence, and shock. More extended hospital stays, higher healthcare costs and charges were found in the SAB cohort. SAB occurring during the index hospitalization of LT-recipients have higher mortality rates than LT-recipients without SAB. More healthcare resources as determined by inflation-adjusted total hospital costs and charges were spent on LT-recipients with SAB compared to those without SAB.